2003
DOI: 10.1080/02650487.2003.11072842
|View full text |Cite
|
Sign up to set email alerts
|

Humour effect on memory and attitude: moderating role of product involvement

Abstract: This study examined the moderating effects of product involvement on the effects of humour on memory and attitude towards the advertisement by using multi-year survey (1992 to 1997) of responses to commercials shown during the Super Bowl. Positive and significant relationships between humorous advertisements on memory and attitude were found through multiple regression analysis. Furthermore, results show that humorous advertisements are more effective in low-involvement products in terms of memory and attitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(59 citation statements)
references
References 43 publications
3
48
0
3
Order By: Relevance
“…This result demonstrates that the use of humour in advertising is effectively an appeal with a high degree of likeability. These results confirm the conclusions of Chung & Zha (2003) and Gulas & Weinberger (2006), which indicate the existence of strong positive relationships between a humorous advertisement and attitude towards the same advertisement.…”
Section: Attitude Of Consumers Towards Creative Appeals In Advertisingsupporting
confidence: 82%
“…This result demonstrates that the use of humour in advertising is effectively an appeal with a high degree of likeability. These results confirm the conclusions of Chung & Zha (2003) and Gulas & Weinberger (2006), which indicate the existence of strong positive relationships between a humorous advertisement and attitude towards the same advertisement.…”
Section: Attitude Of Consumers Towards Creative Appeals In Advertisingsupporting
confidence: 82%
“…Spotts et al (1997) showed improved recall after humorous ads only for lower risk but 'expressive' products, such as snack foods, beer or tobacco products. Likewise, Chung and Zhao (2003) found positive effects only for low-involvement products. Finally, Weinberger and Campbell (1991) showed positive effects only for expressive consumer products advertised with related humour.…”
Section: Introductionmentioning
confidence: 81%
“…Past research suggests that when product involvement is high, consumers have more motivation to devote cognitive effort to evaluating the true merits of a product (e.g., Browne and Kaldenberg, 1997;Celsi and Olson, 1988); consumers neither wish nor are able to make a great deal of effort to process information in a low involvement situation (Chung and Zhao, 2003). Deliberative information processing involves the scrutiny of available information and an analysis of positive and negative features such as, for example, costs and benefits (Fazio, 1990).…”
Section: Product Involvementmentioning
confidence: 99%